“Living Together with Dementia”: construction and conceptual validation of training programme for family caregivers of people with dementia living at home - Sousa, Lia (2016)
Abstract of the research project presented at International Meeting of Doctoral Students in Nursing of Universidade de Lisboa, May 2016.